Variabel Mediasi : Suatu Tinjauan Pengaruh Kualitas Layanan, Customer Experience, dan Kepercayaan terhadap Loyalitas dengan Kepuasan di Puskesmas Berbah Kabupaten Sleman - Rengga Kusuma Putra (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
This research entitle of " Mediating Variables: A Review of the Influence of Service Quality, Customer Experience, and Trust on Loyalty and Satisfaction at the Berbah Public Health Center, Sleman Regency ". The purpose of this study is to find and analyze the influence of service quality, customer experience and trust on loyalty with satisfaction as a mediation variable. To research it uses purposive sampling and accidental sampling of 100 respondents. The tests on this study were conducted with tests of validity, reliability, classical assumptions, hypothesis testing,path analysisand sobel tests. With multiple linear regression analysis in this study obtained results b1 =0.217 showed a positive influence of service quality variables on loyalty, b2 =0.209 showed a positive influence of customer experience variables on loyalty, b3= 0.146 showed a positive influence of trust variables on loyalty, b4 = 0.164 showed a positive influence of satisfaction variables on loyalty. For partial hypothesis testing used t test, obtained a value of tcalculated for the quality of service to loyalty of 4,072, tcount for customer experience to loyalty of 3,648, for trust to loyalty of 2,657 and tcalculate for patient satisfaction to loyalty of 2,657. Then based on the results of calculations through the sobel test, patient satisfaction mediated the relationship between the quality of service to loyalty with at count value of 2,281, patient satisfaction mediated the relationship between customer experience to loyalty with at calculated value of 2,095,patient satisfaction mediated the relationship between trust to loyalty with at count value of 2.0009.